Smart Water Fauced Internet of Things (IoT) - Nicho Ardiwinata, Muhammad; Abdurahman, Donan; Rindri, Yang Agita; Irwan, Irwan (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Efficient and measurable water management is an important global issue in the modern era, especially with rapid population growth and urbanization. The use of conventional water taps often leads to waste, due to bad habits and lack of awareness of water consumption. This study developed the Smart Water Fauced system, an automatic tap equipped with a flow sensor to monitor water consumption in real time. This system is designed to help boarding house residents control water usage and provide boarding house owners with detailed data per room. The research method used is a prototype, which allows for the identification and correction of errors in the early stages of development. The survey results showed that two respondents were satisfied, one respondent was quite satisfied, and one respondent was very satisfied with this system. The implementation of the Smart Water Fauced is expected to reduce water waste, increase user awareness of efficient water use, and create a more equitable and sustainable water resource management system. This innovation contributes to water conservation efforts in the boarding house environment and supports better water resource management in the future.